IJCM_183A: Assessment of treatment adherence among type 2 diabetic patients attending a tertiary care hospital in Madurai district, Tamil Nadu - A cross-sectional study - Akashnath R; Priya S; Muthuraman Kannan (Wolters Kluwer Medknow Publications, 2024)
Background: Type 2 Diabetes Mellitus (DM) is a major public health problem in India affecting around 77 million people above the age of 18 years. Poor adherence to medication regimen increases the probability of micro and macrovascular complications among them thereby increasing the mortality and morbidity. Therefore, assessing adherence is the need of the hour to tide over this crisis and hence present study was conducted Objectives: : 1. To assess the prevalence of treatment adherence among Type 2 DM patients >18years attending tertiary care hospital, Madurai 2. To identify the factors associated with treatment adherence among the study population Methodology: A cross-sectional study was conducted among 208 adult Type 2 DM patients with minimum duration of 6 months attending tertiary care hospital in Madurai during October 2023 by consecutive sampling. Sample size was calculated based on a study in Delhi in 2019. After obtaining informed consent, patients were interviewed using semi-structured questionnaire containing sociodemographic details and Morisky Medication Adherence Scale (MMAS-8), a standard, validated questionnaire to assess treatment adherence. Data was analysed using SPSS version 25.0. Results: The mean age of the participants was 53±10.92 years and majority of them were males (54.8%). 50.5% received primary education and 38.9% belonged to class III Socio-Economic Status (SES). More than half (66.8%) had duration of diabetes between 6months to 3.5 years. 58.2% had good adherence while 29.8% and 12% had moderate and poor adherence respectively. Statistically significant association was not found between adherence and age, gender, SES and duration of diabetes except for the level of education (p value: 0.002). Factors associated with poor adherence were forgetfulness (92%) and being busy (64%). Conclusion: Sustained IEC activities are needed at all levels of health care to further improve the treatment adherence and also addressing the reasons for non-adherence